Smart Devices and Machines for Advanced Manufacturing - Wang, Lihui; Xi, Jeff.; SpringerLink (Online service) (London : Springer London, 2008)
With increasingly complex manufacturing systems and processes, more intelligent and unique devices and machines are needed to support manufacturing operations. Smart Devices and Machines for Advanced Manufacturing presents a focussed collection of quality chapters on the state-of-the-art of research efforts in the area of smart devices and novel machine design, as well as their practical applications to enable advanced manufacturing. The book consists of two major sections, with the first section presenting a broad-based review of several key areas of research in smart devices and machines, whereas the second section is focussed on presenting an in-depth treatment of a particular device or machine, from a parallel kinematic mechanism to a conventional robotic attachment. Smart Devices and Machines for Advanced Manufacturing will be of interest to a broad readership, from manufacturing and industrial engineers to researchers and postgraduates in computer-integrated manufacturing and computer-aided design and manufacturing.
Appropriate Design of Parallel Manipulators -- Gravity Compensation, Static Balancing and Dynamic Balancing of Parallel Mechanisms -- A Unified Methodology for Mobility Analysis Based on Screw Theory -- The Tau PKM Structures -- Layout and Force Optimisation in Cable-driven Parallel Manipulators -- A Tripod-based Polishing/Deburring Machine -- Design and Analysis of a Modular Hybrid Parallel-Serial Manipulator for Robotised Deburring Applications -- Design of a Reconfigurable Tripod Machine System and Its Application in Web-based Machining -- Arch-type Reconfigurable Machine Tool -- Walking Drive Enabled Ultra-precision Positioners -- An XY?Z Planar Motion Stage System Driven by a Surface Motor for Precision Positioning -- Design and Analysis of Micro/Meso-scale Machine Tools -- Micro-CMM -- Laser-assisted Mechanical Micromachining -- Micro Assembly Technology and System.
Keywords: Engineering; Engineering design; Machinery; Control engineering; Robotics; Mechatronics; Manufacturing industries; Machines; Tools; Engineering; Manufacturing, Machines, Tools; Machinery and Machine Elements; Control, Robotics, Mechatronics; Engineering Design; Electronic books